Ventricular tachycardia in patients with type 1 myotonic dystrophy: a case series. Issue 2 (9th June 2019) - Nikhanj, Anish; Sivakumaran, Soori; Miskew-Nichols, Bailey; Siddiqi, Zaeem A; Oudit, Gavin Y
Abstract: Background: Type 1 myotonic dystrophy (DM1) is associated with a variety of cardiac conduction abnormalities and the frequent need for permanent pacing. However, the role of ventricular tachycardia (VT) and the implied risk of sudden cardiac death (SCD) is poorly understood. Case summary: This study examined a 56-patient DM1 cohort of men and women, and identified five patients (two females and three males) with ventricular arrhythmias (8.9%). Patients were reviewed on a case-by-case basis, with their clinical presentation and management of VT and the associated cardiomyopathy indicated. Patient cardiac function was determined by 12-lead electrocardiogram, 48-h Holter monitor, and transthoracic echocardiography. These patients were therefore suitable candidates for implantable cardioverter-defibrillator implantation and received these devices; four of the five patients also received cardiac resynchronization therapy. Medical therapies included angiotensin converting enzyme inhibition, mineralocorticoid receptor antagonist, and following device implantation, beta-blocker therapy was initiated. Discussion: Our case series demonstrates the prevalence of VT in patients with DM1 highlighting the associated risks of SCD in this patient population. The burden of ventricular arrhythmias, advanced conduction disease, and cardiomyopathy are best treated with a combination of device and medical therapies.